Northeast Asian Agriculture: cooperation or competition? - 최세균 (한국농촌경제연구원, 2006)
This paper focuses on the role of the agricultural sector in achieving regional integration in Northeast Asia. Competition between Korea and China in the Japanese import market is increasing. China's agricultural export has significantly increased at the expense of domestic producers in Korea and Japan. All the three Northeast Asian countries have experienced similar structural changes in agriculture, with each country moving towards land saving, and labor or capital intensive farming. They have observed an increase in the share of products with high income elasticity. Each country tries to increase its export of horticultural and small animal products. This paper suggests possible ways of achieving agricultural cooperation in Northeast Asia, while competing each other at the same time. Each country's role in agriculture (i.e. China as a source of food security in the region and a leading exporter, and Japan as a facilitator of trade through import) is stressed. Negotiations over loose form of economic integration are strongly required as a stepping stone for further economic integration to discuss agricultural issues such as trade facilitation, e.g. standards, labeling, customs procedures/ administration and economic and technology cooperation. The terminology of negotiation or bargaining, though not friendly to those in the losing sectors, is similar to the meaning of cooperation based on competition.
Keywords: Northeast Asia; FTA; negotiation; cooperation; structural change; competitiveness; trade facilitation.; Northeast Asia; FTA; negotiation; cooperation; structural change; competitiveness; trade facilitation.